2022
DOI: 10.3389/fpsyt.2022.941575
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of the COVID-19 Pandemic on Smoking Consumption: A Systematic Review of Longitudinal Studies

Abstract: The COVID-19 pandemic has generated a global health crisis that has negatively impacted the mental health and wellbeing of the population. A large amount of scientific literature has emerged since 2019, but none of these studies have focused on assessing the impact of COVID-19 on smoking consumption. We aimed to analyse the changes in smoking consumption during the COVID-19 pandemic through longitudinal studies. This systematic review follows the PRISMA Statement. This study was registered on PROSPERO (CRD4202… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
20
2

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(25 citation statements)
references
References 49 publications
3
20
2
Order By: Relevance
“…Of these, 25 papers related to mental health impacts, 13 to healthcare delivery, 12 to infection control, 13 to economic impacts, 7 to social impacts, and 3 to impacts on education. In addition, we identified systematic reviews of impacts on mental health [ 87 , 88 , 89 , 90 , 91 ], physical activity [ 46 , 65 , 92 , 93 , 94 ], diet and nutrition [ 47 , 65 , 66 , 67 , 68 ], body weight and obesity [ 48 , 71 , 72 ], alcohol consumption [ 49 ], and tobacco smoking [ 50 , 95 ], which we present in summary below, along with individual primary research papers of particular interest.…”
Section: Review Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Of these, 25 papers related to mental health impacts, 13 to healthcare delivery, 12 to infection control, 13 to economic impacts, 7 to social impacts, and 3 to impacts on education. In addition, we identified systematic reviews of impacts on mental health [ 87 , 88 , 89 , 90 , 91 ], physical activity [ 46 , 65 , 92 , 93 , 94 ], diet and nutrition [ 47 , 65 , 66 , 67 , 68 ], body weight and obesity [ 48 , 71 , 72 ], alcohol consumption [ 49 ], and tobacco smoking [ 50 , 95 ], which we present in summary below, along with individual primary research papers of particular interest.…”
Section: Review Resultsmentioning
confidence: 99%
“…Regarding tobacco use, there were some studies with somewhat encouraging findings. For instance, in a systematic review of longitudinal studies that identified 14 cohorts in 11 published papers, with a total of 58,052 participants, Almeda et al (2022) [ 50 ] found that most studies indicated a reduction in the number of cigarettes and e-cigarettes consumed from before to during the pandemic. They found that studies with the highest mean daily stringency index for NPIs (in the UK, China, US, Pakistan, and Spain) detected reductions in the percentage of smokers [ 50 ].…”
Section: Review Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The impact of the COVID-19 pandemic on smoking behaviour is complex and unclear. A recent systematic review that included 11 publications (58 052 participants) found that smoking consumption decreased during the pandemic in most cases [ 95 ]. Fear and social restrictions could be leading to an excellent opportunity to reduce or quit smoking.…”
Section: Smoking Cessation During the Coronavirus Disease 2019 Pandem...mentioning
confidence: 99%